Complaints management in the pharmaceutical industry: A Case Study - Marija Stojanovska; Maja Poposka-Stojchevska; Gordana Mitrovska; Stevce Petrovski; Katerina Brezovska (Makedonsko Farmacevtski Bilten)
Effective complaints management in the pharmaceutical industry is one of the cornerstones for ensuring product quality, regulatory compliance, and customer safety and satisfaction. Adequate handling of complaints ensures not only compliance with regulatory standards, but also maintenance of public confidence, the company’s reputation, and a continuous improvement of product quality. To ensure proper complaint management we must understand the importance of providing an effective complaint management system, the regulatory obligations framing it, and the processes of handling complaints, focusing on involving best practices and the potential challenges pharmaceutical companies face. This paper describes the process of handling a complaint that a pharmaceutical company has received from a foreign regulatory agency. The complaint referred to a burning sensation in the eyes after applying an eye ointment containing 1% chloramphenicol and a change in the smell of the ointment. After conducting an extensive investigation, the quality of the product was confirmed and it was demonstrated that there is no risk to patient health.